The Aesthetics of Calligraphic Decorations in the Manuscript Qur’an and Archaeological Scenes until the fall of The Abbasid Caliphate in 656 AH (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The art of manuscripts or the art of the Qur’an is one of the important topics in the field ofIslamic archaeology in general and decorative arts in particular, and it forms the main basis forstudying the arts of the book. This study presents the aesthetics of calligraphic decorations, howthey developed and the many aesthetics they carry, as it was a vast field to show the ingenuity ofthe Muslim artist, and that wealth that is treasured by manuscripts, especially the Noble Qur’anand archaeological scenes, because of the arts they contain in the field of calligraphy anddecoration, which enriches archaeological studies through the diversity of Islamic decorationforms, the most important of which are vegetal, geometric and calligraphic decorations, and theirforms used in a new artistic style.